Allograft Alone vs. Allograft with Intramedullary Vascularized Fibular Graft for Lower Extremity Bone Cancer: A Systematic Review and Meta-Analysis. Issue 7 (July 2020) - Othman, Sammy; Bricker, Jonathan T.; Azoury, Saïd C.; Elfanagely, Omar; Weber, Kristy L.; Kovach, Stephen J.
Abstract: Background: Limb salvage surgery has become a first-line treatment in the setting of lower extremity cancer. Despite a multitude of techniques, the most effective modality for osseous reconstruction has not been described. We aim to examine outcomes of allograft reconstruction alone compared to an allograft combined with a vascularized fibula graft (VFG) (Capanna Technique) through a meta-analysis of the literature. Methods: A systematic review of the literature was conducted through the online databases PubMed, Embase, and Web of Science, examining articles utilizing an allograft with or without an intramedullary VFG for the reconstruction of lower extremity osseous defects following oncological resection. A meta-analysis examined outcomes, including nonunion, infection, fractures, explantation, and functional limb status, that were evaluated dependent upon reconstructive modality. Results: Twenty-five articles were deemed appropriate for inclusion. The allograft with VFG group had considerably lower rates of nonunion (13%) in comparison to the allograft alone group (21.4%) (p < .001). Rates of infection (7.9% vs. 9%, respectively) and fracture (19.6% vs. 19.1%) were not statistically different. The allograft with VFG group also had significantly lower rates of explantation (6.57%) compared to the allograft alone cohort (18.11%) (p < .001). Functional outcomes were similar across groups as measured by Musculoskeletal Tumor Society scores (88.22% vs. 87.77%). Conclusions: Allograft reconstruction with a supplementary inlay VFG decreases the risk of nonunion and explantation compared to allograft alone reconstruction in the setting of oncological resection of the osseous lower extremity. This technique warrants increased consideration in the operative planning of lower limb reconstruction following tumor extirpation.